CURRENT STATE AND MAIN DEVELOPMENT TRENDS OF THE POULTRY INDUSTRY IN UZBEKISTAN (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2026)
This article examines the current state and major development trends of the poultry industry in Uzbekistan. The study analyzes recent changes in poultry meat and egg production, the expansion of poultry farms, and the role of the sector in ensuring food security and supporting agricultural diversification. Particular attention is given to government support measures, investment activity, modernization processes, and the introduction of innovative technologies in poultry production. The research also evaluates existing challenges related to feed supply, production efficiency, veterinary safety, and export competitiveness. Based on the analysis, the article identifies the main factors influencing the sustainable development of the poultry industry and outlines prospective directions for improving the sector’s economic efficiency and export potential.
Keywords: poultry industry, poultry farming, poultry meat production, egg production, food security, agricultural development, export potential, innovative technologies, livestock sector, Uzbekistan economy.